Menuju Kerangka Multidimensional-Dialektis Pembelajaran PAK di Perguruan Tinggi: Sintesis Perspektif AECT 2023 - Michael Rahankey (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2026)
This article aims to formulate a multidimensional-dialectical framework for Catholic Religious Education (CRE) learning in higher education by synthesizing five dimensions of learning from the perspective of the AECT (2023) definition of Educational Technology. This study is grounded in the view that CRE learning cannot be understood merely as the delivery of content, but rather as a pedagogical practice that interrelates formative goals, communication, systems, technology, and ethical responsibility. Using a conceptual-critical approach, this article maps learning into systemic, communicative, teleological, technological, and ethical dimensions, while also examining the tensions that arise among them, such as structure and flexibility, efficiency and dialogue, learning outcomes and character formation, as well as innovation and ethical caution. The synthesis shows that the AECT (2023) definition provides an integrative, human-centered basis for a more holistic understanding of learning. This article concludes that tensions among dimensions are not obstacles to eliminate but rather dynamics that need to be managed reflectively through the design, implementation, and evaluation of learning. This framework may serve as a conceptual foundation for developing CRE learning that is more integrated, humane, and contextual.